1998
DOI: 10.1093/gerona/53a.1.m20
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Cytokine Production in an Elderly Population: Effect of Age and Inflammation

Abstract: Production of IL-6 and IL-1Ra--but not IL-1 beta or TNF-alpha--was increased in the elderly compared to healthy, young subjects. The increase in IL-6 also correlated with increased production of CRP, a marker of inflammation. However, IL-1Ra was increased in the elderly independently of CRP production. Although limited by the small control group, these data suggest that dysregulation of some inflammatory cytokines occurs with age, but the role of inflammation in aging remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
221
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(249 citation statements)
references
References 39 publications
19
221
1
4
Order By: Relevance
“…Even though cytokine levels may differ in elderly patients, it seems unlikely that the greater age in this patient group is decisive for the observed mismatch in IL-1b and IL-1RA secretion. Population studies revealed increased production of IL-1RA from blood mononuclear cells in the elderly, whereas IL-1b levels remained unchanged on ageing [23].…”
Section: Discussionmentioning
confidence: 97%
“…Even though cytokine levels may differ in elderly patients, it seems unlikely that the greater age in this patient group is decisive for the observed mismatch in IL-1b and IL-1RA secretion. Population studies revealed increased production of IL-1RA from blood mononuclear cells in the elderly, whereas IL-1b levels remained unchanged on ageing [23].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, ox-LDL has also been shown to stimulate IL-6 expression (Massy et al 2000) and IL-1β release (Thomas et al 1994). Additionally, in vitro studies have shown that monocytes from elderly individuals are in a preactivated state; there is greater initial production of proinflammatory cytokines, but there is no difference in the peak levels of cytokines among elderly and younger subjects (Ahluwalia et al 2001;Roubenoff et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The data regarding cytokine and chemokine secretion are ambiguous in several studies using human monocytes from aged or young individuals activated in vitro with mitogens or LPS. Although the majority of the studies indicate an increase in the levels of pro-inflammatory factors such as IL-6 and IL-8 (Ershler et al ., 1993;Clark & Peterson, 1994;O'Mahony et al ., 1998;Roubenoff et al ., 1998;Sadeghi et al ., 1999;Hasegawa et al ., 2000;Mariani et al ., 2002), others find decreased levels (Gon et al ., 1996;Beharka et al ., 2001) or no changes at all (Ahluwalia et al ., 2001). Differences in the genetic heterogeneity and health status of the test population, in addition to the experimental and assay conditions, may all contribute to the discrepancy in these results.…”
Section: Cytokine and Chemokine Secretionmentioning
confidence: 99%